Interview with Associate Professor of Rijeka University Iva Rinčić: (The Interview has been conducted by Hanna Hubenko in terms of the International Conference «The 21st Rijeka Days of Bioethics. Urban Bioethics: From Smart to Living Cities. Bioethical Debate, Reflections and Standards», Rijeka, Croatia, 17 – 18 May 2019) - Hubenko, Hanna; Rinčić, Iva (Filosofiya osvity. Philosophy of Education, 2019)
Interview with associate professor Iva Rincic feels like meeting a close-minded person on a very long journey. Meet and feel that you are “on the same page”. What is urban bioethics? How is it different from bioethics in general? What is this “Project on Bioethical Urban Life Standards: The City as the Basis for Ethics Life”? – are the main points laid down in the conversation. So, during the interview, you will find out that despite the fact that bioethics is perceived as a modern version of biomedical ethics, originally it covers a much wider area of ​​interest. Bioethics implies moral obligations of people not only to each other, but also to everything living (animals and plants) (F. Jahr (1926)). This is the science of survival (V. R. Potter (1971)). If we see bioethics in this way, then urban life is necessary as a (bio) ethical object, purpose and scope, and "the city as a living creature that is constantly growing and transforming." Within the framework of the project the main goal is to create a list of urban bioethics standards. In order to activate the mechanism of urban bioethics, Iva talks about such valuable characteristics of local people as Responsibility, Committment, Awareness, Trust, Belonging. The project “European Bioethics in Action” fed into the list of bioethical standards. Iva Rincic also presented a list of 97 standards that determine relationships between animals, plants, people and environment. Further this list will be simplified for residents of the city. Iva wants all citizens to be included in these lists. She is also sure that this is the only way to have a rather bright tool to achieve bioethical city in the future.